Characteristics of Long‐Term Care Residents That Predict Adverse Events after Hospitalization. Issue 11 (20th August 2020) - Kapoor, Alok; Field, Terry; Handler, Steven; Fisher, Kimberly; Saphirak, Cassandra; Crawford, Sybil; Fouayzi, Hassan; Johnson, Florence; Spenard, Ann; Zhang, Ning; Gurwitz, Jerry H.
Abstract : BACKGROUND/OBJECTIVES: Adverse events (AEs) occur frequently in long‐term care (LTC) residents transitioning from the hospital back to an LTC facility. Measuring the association between resident characteristics and AEs can inform AE risk reduction strategies. DESIGN: Prospective cohort analysis. SETTING: A total of 32 nursing homes from six New England states. PARTICIPANTS: A total of 555 LTC residents contributing 762 transitions from the hospital back to LTC. MEASUREMENTS: We measured the association between all AEs and preventable AEs developing in the 45 days following discharge back to LTC and demographic variables, hospital length of stay (LOS), Charlson Comorbidity Index (CCI) (0–1, 2–3, 4–5 and ≥6), dependency in activities of daily living (ADLs) using the Minimum Data Set Long Form Scale (in quintiles 0–12, 13–15, 16, 17–18, and ≥19), and number of regularly scheduled medications (0–9, 10–13, 14–17, and ≥18). To understand the independent association of each resident characteristic with AEs and preventable AEs, we constructed multiple Cox proportional hazards models. RESULTS: There were 283 discharges with one or more AEs and 212 with preventable AEs. Characteristics independently associated with higher risk of an AE included hospital LOS 9 or more days (hazard ratio [HR] = 1.49; 95% confidence interval [CI] = 1.02–2.17); CCI of 4 to 5 (HR = 1.74; 95% CI = 1.13–2.67) or 6 or higher (HR = 1.58; 95% CI = 1.01–2.46); 18 or more regularly scheduled medications (HR = 1.53; 95% CI = 1.07–2.18); and 19 and above on ADL dependency (HR = 1.78; 95% CI = 1.21–2.62). Results from models with preventable AEs were similar to those with all AEs. CONCLUSION: Increased LOS, higher comorbidity burden, greater dependency in ADLs, and polypharmacy were the resident characteristics most strongly associated with risk of AEs and preventable AEs. We recommend heightened vigilance in the care of LTC residents with these characteristics transitioning back to LTC. We also recommend research to assess strategies to reduce the risk of AEs.